Neurosafety and Oncotropism of the Oncolytic Farmington Virus in the Treatment of Glioblastoma Multiforme - Skillings, Robyn (Université d'Ottawa / University of Ottawa, 2020)
Glioblastoma multiforme is the most common and malignant form of brain cancer in humans. The current prognosis for glioblastoma patients undergoing standard treatment is extremely low, with a median patient survival of 1 to 2 years. Oncolytic viruses are currently being evaluated as promising novel therapies for the treatment of glioblastoma. Our laboratory’s preliminary data has demonstrated that the oncolytic rhabdovirus Farmington effectively eliminates brain tumours, but is also neurosafe. However, the biological mechanisms underlying Farmington’s neurosafety and oncotropism were unknown. Through studying Farmington infection in normal brain cells and brain cancer cells in vitro, we determined that Farmington’s distinct tropism is dependent on the Farmington glycoprotein and the type 1 interferon response.
Keywords: Oncolytic virus; Glioblastoma; Virology; Viral glycoprotein; Neurosafety; Interferon; Oncotropism; Rhabdovirus